The Relevance of the Basic Philosophy of Education in Answer Challenges of Education in the Digital Era - Samsudin Samsudin (Prodi PGMI STIT Sunan Giri Bima, 2026)
Education requires runway strong philosophy to be able to answer various challenges that arise consequence development technology, globalization, and change social in the digital age. This article aim analyze relevance basics philosophy education that includes ontology, epistemology, and axiology in face dynamics education contemporary research​ use approach qualitative with type study library research. Data obtained from books, articles scientific, and documents relevant academic​ with philosophy education and modern education, then analyzed use technique content analysis. Study results show that ontology education put man as subject the main thing that must be developed in a way intact through the process of humanization. Epistemology education confirm importance development critical, reflective, and relevant knowledge with the needs of the times, while axiology education functioning as runway in formation values, morals, and character participant educate. Third dimensions the each other related and become foundation in build system humanistic, adaptive, and development-oriented education man in its entirety. This article offer synthesis conceptual about relatedness ontology, epistemology, and axiology as framework relevant philosophy​ for answer challenge digital era education.